Incidencia de la motivación salarial en la constructora Andrade Rodas de la ciudad de Quito. - Vásquez Otáñez, Karen Soffia (2019)
The purpose of this research is to determine the incidence of salary motivation at working performance, by an Econometric Model that contributes with the identification of factors that affect to the normal development of carried out activities by Andrade Rodas construction company in Quito city. Evaluating the performance of a collaborator is a fundamental component for companies, because it helps to implement strategies and refine the efficiency, however the measurement of working performance must be based on a serie of fundamental principles where an in situ visit was made. here a technique called focus groupal was applied to the employees, to collect necessary information and data through a structured questionnaire; once analyzed, it can be mentioned that the most important factors that affect working performance are: environment, setting goals and objectives, worker adaptation, necessary tools and openness to the experience, while the aspects that should be taken in account into the company related to salary motivation are: schedules, communication, money, economic stability or salary. It is necessary to take into account that now Human Resources play a very important role at the organization, so it is important to ensure the welfare of each employee in the company, for which a qualitative approach was used, being a method that allowed the collection of information, it was possible to know the relationship that exists between the established variables at the research, work performance and salary motivation. It is important to indicate that one of the main beneficiaries of this researching work are the workers since new experiences and opportunities those can be established inside the company, at the same way the identification of factors that will contribute with the top company management to motivate employees and for future evaluations of working performance.